2018
DOI: 10.3847/1538-4357/aaab60
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation Fornax Survey (NGFS). II. The Central Dwarf Galaxy Population

Abstract: We present a photometric study of the dwarf galaxy population in the core region (≲ r vir 4) of the Fornax galaxy cluster based on deep u ′ g ′ i ′ photometry from the Next Generation Fornax Cluster Survey. All imaging data were obtained with the Dark Energy Camera mounted on the 4-meter Blanco telescope at the Cerro-Tololo Interamerican Observatory. We identify 258 dwarf galaxy candidates with luminosities −17 ≲ M g ′ ≲ −8 mag, corresponding to typical stellar masses of 9.5 ≳ log M ⋆ M ⊙ ≳ 5.5, reaching ∼ 3 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(152 citation statements)
references
References 218 publications
9
117
0
Order By: Relevance
“…Although NSCs are very common in all types of galaxies (e.g. Georgiev et al 2009a;Eigenthaler et al 2018), their formation is still under debate and two main pathways are usually discussed. In the GC accretion or GC in-spiral scenario, the NSC builds out of the (dry) mergers of GCs that migrate into the galaxy's centre due to dynamical friction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although NSCs are very common in all types of galaxies (e.g. Georgiev et al 2009a;Eigenthaler et al 2018), their formation is still under debate and two main pathways are usually discussed. In the GC accretion or GC in-spiral scenario, the NSC builds out of the (dry) mergers of GCs that migrate into the galaxy's centre due to dynamical friction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Fornax cluster has recently been at the centre of several major observing programmes over a wide range of wavelengths. This includes deep optical imaging (Iodice et al 2016;Venhola et al 2018;Eigenthaler et al 2018), optical integral field unit (IFU) observations of selected targets (Scott et al 2014;Mentz et al 2016;Sarzi et al 2018), ALMA observations (Zabel et al 2019;Morokuma-Matsui et al 2019), far-infrared Herschel imaging (Davies et al 2013) and, at radio wavelengths, a survey carried out with the Australia Telescope Compact Array (ATCA; Lee-Waddell et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous NGFS papers (Muñoz et al 2015;Eigenthaler et al 2018;Ordenes-Briceño et al 2018a), we reported the detection of the extended sources in the Fornax cluster from the RGB full-color image; in total, there are 643 dwarf galaxies which are very likely to be the members of the Fornax cluster (according to their locations in the color-magnitude diagrams, morphologies, and sizes; see Eigenthaler et al 2018 for details), including the known 299 ones from previous works (Ferguson 1989;Mieske et al 2007). Among the 643 dwarfs, seven galaxies are ultradiffuse galaxies (UDGs; van Dokkum et al 2015;Rong et al 2017a).…”
Section: Alignments Of the Fornax Dwarfs 21 Photometrymentioning
confidence: 98%
“…The deep multiwavelength Next Generation Fornax Survey (NGFS; Muñoz et al 2015), covering the entire Fornax galaxy cluster out to its virial radius (R vir 1.4 Mpc, Drinkwater et al 2001), provides the u , g , and i -band photometries (reaching pointsource detections with S/N∼ 5 at 26.5, 26.1, and 25.3 mag, respectively) obtained with the Dark Energy Camera (DE-Cam;Flaugher et al 2015) mounted on the 4m Blanco telescope at Cerro Tololo Interamerican Observatory (CTIO) and J and K s -band photometry from VIRCam mounted on the 3.7 m VISTA at ESO's Paranal Observatory (Sutherland et al 2015). NGFS encompasses the unprecedented accuracy to study the properties of the extremely-faint and low-mass objects (∼ 10 6 M ) in the nearby cluster, including the stellar masses and ages of the nuclear star clusters (NSCs) in the nucleated dwarf galaxies (Ordenes-Briceño et al 2018b), color distributions of NSCs and dwarf spheroids (Eigenthaler et al 2018), dwarf clustering (Ordenes-Briceño et al 2018a), and in particular, morphologies of dwarfs. Further, since the morphologies of dwarfs are relevant to their properties and environments, e.g., the presence of NSCs, galactic luminosities/stellar masses, and their locations in galaxy clusters/groups (e.g., Sánchez-Janssen et al 2019Roychowdhury et al 2013), it is reasonable to compare the alignment signals of the NGFS dwarfs with the different properties.…”
Section: Introductionmentioning
confidence: 99%